FORMATION OF GENDER COMPETENCE IN THE PROCESS OF TRAINING FUTURE SOCIAL WORKERS - KRAVCHENKO, Oksana; VOITOVSKA, Alla (Social work and education, 2024)
The article highlights the need to develop gender competence in future social work professionals and the use of an integrated approach in this field. The study aims to theoretically substantiate the peculiarities of gender competence formation in future social workers. The implementing possibilities for the Strategy of Gender Equality in Education until 2030 have been identified. The availability of gender studies in institutions of higher education has been analyzed. It is stated that domestic training programmes have the gender component included in curricula of various specialities. The studies in the field of gender equality and social work demonstrate that although there are specific disciplines that include aspects of preventing discrimination and violence against women, they need updating and adapting to modern challenges. The article analyses training and scientific programmes in the speciality “231 Social Work” in terms of content and specifics of preparing specialists to perform their duties taking into account the requirements of gender equality. It has been found that most of them are based on the requirements of state standards for the formation of competencies in human rights and anti-discrimination. It is emphasized that Pavlo Tychyna Uman State Pedagogical University has established Gender Centre that is a member of the All-Ukrainian Centre for Gender Education in Ukraine. Training future specialists in the specialty “231 Social Work”, forming their ability to carry out professional activities in compliance with human rights and the principle of gender equality, and developing competencies in preventing and combating gender discrimination are among the Centre’s main tasks. The author substantiates the need to form gender competence in future social workers by including a gender approach in the educational process as specialised disciplines revealing applied aspects of gender equality and participation in non-formal education play an important role there.